2017
DOI: 10.1021/acs.joc.7b01817
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Immunological Comparison of Differently Linked Lipoarabinomannan Oligosaccharide–Monophosphoryl Lipid A Conjugates as Antituberculosis Vaccines

Abstract: A monophosphoryl lipid A (MPLA) derivative having the 6'-OH group substituted with an NH group was synthesized and coupled with the upstream terminal tetrasaccharide of mycobacterial lipoarabinomannan (LAM) via an amide bond to create a novel type of MPLA-based fully synthetic glycoconjugate vaccine. The same tetrasaccharide was also coupled with MPLA at the 1-O-position. Immunological activities of the two synthetic conjugates were evaluated in mice and compared. Both afforded robust overall and IgG antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 75 publications
1
34
1
Order By: Relevance
“…In the aforementioned MPLA based vaccine designs, the antigens were all conjugated with MPLA through 1-O-position instead of 6 ′ -O-position where the polysaccharide chain is attached to LPS in nature (Wang et al, 2017). Guo and Gu further studied the influence of different antigen linkage positions on immunological properties (Schemes 2B,C), by linking a tetrasaccharide antigen from lipoarabinomannan (LAM), a Mycobacterium tuberculosis cell surface lipopolysaccharide, to either 1 or 6 ′ position of MPLA.…”
Section: Mplamentioning
confidence: 99%
“…In the aforementioned MPLA based vaccine designs, the antigens were all conjugated with MPLA through 1-O-position instead of 6 ′ -O-position where the polysaccharide chain is attached to LPS in nature (Wang et al, 2017). Guo and Gu further studied the influence of different antigen linkage positions on immunological properties (Schemes 2B,C), by linking a tetrasaccharide antigen from lipoarabinomannan (LAM), a Mycobacterium tuberculosis cell surface lipopolysaccharide, to either 1 or 6 ′ position of MPLA.…”
Section: Mplamentioning
confidence: 99%
“…Lipoarabinomannan (LAM) and related arabinogalactan (AG) are two major structural components of the M. tuberculosis cell wall. Previous studies revealed that LAM and especially its terminal oligosaccharide fragments, conjugated with proteins [7,10,19] or monophosphoryl lipid A [23], are attractive targets for the development of carbohydrate-based anti-TB vaccines [7,10,19,23,65,66].…”
Section: Tuberculosis (Tb) Which Is Caused By the Pathogenic Bacterimentioning
confidence: 99%
“…Some bacterial glycans [1,2] are specific markers for detection and serological identification of microorganisms [3][4][5] and are widely used as antigenic components of vaccines [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The use of gold nanoparticles (GNPs) [24][25][26] as carriers for glyco-epitopes is becoming an important alternative [15, to the traditional conjugation with proteins, synthetic polymers and other carriers [15,17,38,[49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…A number of bacterial glycans [1,2] are specific markers for the detection and the serological identification of microorganisms [3][4][5] and are widely used as antigenic components of vaccines [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The use of gold nanoparticles (GNPs) [24][25][26] as carriers for glyco-epitopes is becoming an important alternative [15, to the traditional conjugation with proteins, synthetic polymers and other carriers [15,17,38,[49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Lipoarabinomannan (LAM) and the related arabinogalactan (AG) are two major structural components of the M. tuberculosis cell wall. Previous studies revealed that LAM and especially its terminal oligosaccharide fragments, conjugated with proteins [7,10,19] or monophosphoryl lipid A [23], are attractive targets for the development of carbohydrate-based anti-TB vaccines [7,10,19,23,65,66].…”
Section: Introductionmentioning
confidence: 99%